Model Pengelolaan Sampah Rumah Tangga di Desa Pejaten Kecamatan Kramatwatu - Rizky Anugrah, Indra; Alfariz, Muhamad Zaky; Sapoe, Timotius Christian; Sahrupi, Sahrupi (Metode : Jurnal Teknik Industri, 2025)
Pejaten Village in Kramatwatu Sub-district faces a major challenge in household waste management with an ever-increasing volume of waste that could reach 300.73 tons per month by 2024. This increase is influenced by rapid population growth and low public awareness of the negative impacts of littering. The habit of disposing of waste in open areas and the lack of understanding about the importance of good waste management exacerbate the condition. This study aims to identify the main factors that cause high waste generation using the Causal Loop Diagram (CLD) approach. This approach allows mapping the cause-and-effect relationships of various variables that contribute to the problem, including unsustainable consumption patterns, limited waste management facilities, and low public awareness of environmental hygiene. The results show a complex interrelationship between environmental quality, availability of transport fleets, and community awareness. This research confirms the need for more structured and sustainable intervention measures in waste management, such as community education on the importance of sorting waste, improving waste management facilities, and optimizing the waste transportation system. It is hoped that these efforts can produce effective solutions to reduce the volume of waste, improve the quality of the environment in Pejaten Village, and build collective awareness of shared responsibility in maintaining environmental cleanliness.